Modelling extreme precipitation in hazardous mountainous areas. Contribution to landscape planning and environmental management - Pereira, Paulo; Oliva, Marc; Baltrėnaitė, Edita (Journal of Environmental Engineering and Landscape Management, 2010)
Extreme precipitation episodes are very common in Mediterranean area and can lead to serious and catastrophic environmental hazards. They have special incidence during autumn months, September, October and November (SON) with important impacts on society, leading frequently to significant economic losses and mortality. These events have special impact in mountainous areas where steep slopes enhance the effects of extreme precipitation. In mountainous areas rain gauge stations are sparse and normally in lower amount. Due to these reasons it is very important to map with higher accuracy the distribution of extreme precipitation. Also, in mountainous environments precipitation patterns can change in small distances that make the prediction more difficult, but also more important. A better prediction of areas with higher values of extreme precipitation will contribute to a better land use planning and avoid the effects of flash floods, land‐slides and soil erosion recognized as environmental problems. The aim of this paper is testing several well‐known interpolation methods, Inverse Distance Weight (IDW) with weighs of 1, 2, 3, 4 and 5, Local Polynomial (LP) with order 1 and 2, Radial Basis Methods (RBS), particularly Spline With Tension (SPT) and Thin Plate Spline (TPS), and Kriging techniques, Ordinary Kriging (OK) and Ordinary CoKriging (COK) in order to identify the less‐biased method to interpolate extreme precipitation calculated from the 95th percentile (P95) of SON precipitation in a mountainous area located in Portugal. The results show that extreme precipitation increases with the altitude and there are important differences between stations located at higher and lower altitudes. This relation is observed in the omni‐directional semi‐variograms calculated where we identified two major P95 areas coincident with higher elevations. The first one occurred at 12.19 km and the second at 23.57 km. The higher values of P95 are identified at Southeast and Northeast. In contrast, the lower P95 values are identified at Northwest due to lower altitudes and in the Northeast corner as a consequence of rain shadow effect. Prediction with precision of precipitation patterns in mountainous areas is difficult due to lack of data and the complex effect of topography in rainfall, however, it is of major importance in order to identify vulnerable areas. The findings observed in this study are a fundamental contribution to landscape planning and environmental management in areas with higher occurrence and vulnerability to extreme precipitation.Article in English.Gausių kritulių pasiskirstymo poveikio pavojingose kalnų vietovėse modeliavimas. Pagalba planuojant kraštovaizdį, aplinkos valdymąSantrauka. Gausūs krituliai, ypač būdingi Viduržemio jūros regionui, gali kelti rimtų pavojų aplinkai, lemti katastrofas. Kritulių poveikio zona ypač išsiplečia rudens laikotarpiu, t. y. rugsėjo, spalio ir lapkričio (RSL) mėnesiais, neretai patiriama didelių ekonominių nuostolių, žūsta ar kitaip nukenčia žmonės. Statūs kalnų šlaitai sustiprina gausių kritulių poveikį. Kalnuotose vietovėse kritulių kiekio stebėjimo stočių nedaug, jos toli viena nuo kitos, todėl labai aktualu turėti žemėlapius, tiksliai nusakančius gausių kritulių pasiskirstymą. Kalnuotose vietovėse krituliu pobūdis skirtingų atstumu gali būti skirtingas, kritulių kieki numatyti sunkiau, tačiau tai itin svarbu. Tiksliau numatant vietoves, kur iškrenta daugiau kritulių, galima tikslingiau planuoti žemėtvarką, išvengti staigiu potvynių, nuošliaužų ir dirvožemio erozijos. Tyrimo tikslas buvo patikrinti kelis gerai žinomus interpoliacijos metodus – Inverse Distance Weight (IDW) su 1–5 svertinemis vertėmis, Local Polynomial (LP), Radial Basis (RBS), ypač Spline With Tension (SPT), Thin Plate Spline (TPS), – bei Kriging technikas ir Ordinary Kriging (OK) bei Ordinary CoKriging (COK) metodus, siekiant parinkti tiksliausią, kuris leistų interpoliuoti gausius (95 %) kritulius RSL mėnesiais kalnuotoje Portugalijos teritorijoje. Nustatyta, kad kritulių kiekis didėja didėjant altitudei. Reikšmingi kritulių skirtumai nustatyti stotyse, esančiose skirtinguose aukščiuose virš jūros lygio. Šis santykis pastebėtas visomis kryptimis apskaičiuotose pusinėse variogramose. Jose išsiskiria dvi teritorijos, kurių P95 vertes didžiausios, ir akivaizdi sąsaja su dildelėmis altitudemis. Pirmoji teritorija 12,19 km, o antroji 23,57 km aukštyje. Didžiausios P95 vertes pietryčių ir šiaurės rytų kryptimis, mažiausios – šiaurės vakarų kryptimi, kur altitudės mažos, ir šiaurės rytų teritorijos kampe dėl lietaus “šešėlio” efekto. Tiksliai numatyti kritulių pobūdį kalnuotose teritorijose apsunkina duomenų trūkumas ir sudėtinga topografijos įtaka krituliams. Rezultatai ypač parankūs planuojant ir valdant dažniems ir gausiems krituliams jautrias teritorijas.Reikšminiai žodžiai: gausūs krituliai, pavojus aplinkai, Viduržemio regionas, rugsėjis, spalis, lapkritis (RSL), kalnuotos vietovės, interpoliacijos metodai, kraštovaizdžio planavimas ir aplinkos valdymas.Моделирование влияния распределения обильных осадков в опасных горных местностях. Помощь в планировании ландшафта и управлении окружающей средойРезюме. Обильные осадки, особенно характерные для Средиземноморского региона, могут быть опасными для окружающей среды. Зона влияния осадков особенно увеличивается в осенний период – сентябре, октябре и ноябре. Осадки зачастую вызывают большие экономические убытки, гибнут или страдают люди. Влияние обильных осадков усиливают крутые горные склоны. В горных местностях станций наблюдения за количеством осадков немного и расположены они далеко друг от друга, поэтому необходимы карты, на которых было бы точно указано распределение обильных осадков. Характер осадков в горных местностях в зависимости от удаленности может значительно различаться, предвидеть количество осадков чрезвычайно сложно, однако это жизненно необходимо. Зная местности, на которых ожидается большее количество осадков, можно точнее планировать землеустройство, избежать внезапных наводнений, оползней и эрозии почв. Целью исследования было проверить несколько хорошо известных методов интерполяции – Inverse Distance Weight (IDW) с 1–5 значениями весомостей, Local Polynomial (LP), Radial Basis (RBS), особенно Spline With Tension (SPT), Thin Plate Spline (TPS), а также технику Kriging, методы Ordinary Kriging (OK) и Ordinary CoKriging (COK) с целью выявить наиболее точный, с помощью которого можно было бы интерполировать обильные (95%) осенние осадки в горных местностях Португалии. Установлено, что количество осадков увеличивается с увеличением амплитуды. Значительная разница в количестве осадков выявлена на станциях, находящихся на разной высоте от уровня моря. Это соотношение замечено на всех направлениях рассчитанных полувариограмм. На них выделяются две территории, на которых значения P95 наиболее велики и очевидна связь с большими амплитудами. Первая территория находится на высоте 12,19 км, вторая – 23,57 км. Наибольшие значения P95 отмечены в юго-восточном и северо-восточном, наименьшие – северо-западном направлениях, где амплитуды малы, и в углу северо-восточной территории из-за эффекта «тени» дождя. Точнее предвидеть характер осадков в горных местностях представляется затруднительным из-за недостатка данных и сложного влияния на осадки топографии. Результаты исследования окажутся особенно полезными при планировании и управлении территориями, подвергаемыми частым и обильным осадкам.Ключевые слова: обильные осадки, опасность для окружающей среды, Средиземноморский регион, осенний период, горная местность, методы интерполяции, планирование ландшафта и управление окружающей средой.First Publish Online: 10 Feb 2011